MODIFIKASI DRUM PULLEY UNTUK MENGURANGI RETAK PADA SAMBUNGAN SIDE PLATE DENGAN AUTODESK INVENTOR - Akbar, Muhammad Faisal; Andrianto, Sis Nanda Kus; Riyanto, Obaja Eden Sentosa (Journal of Industrial Engineering & Technology Innovation, 2025)
The Industrial Work Practice (PKL) implemented at PT Semen Gresik Rembang focused on identifying and repairing technical problems in the drum pulley component, which often experiences cracks in the side plate welding area. Damage to this component disrupts the smooth operation of the factory because it hampers the production process. The main objective of this study is to modify the drum pulley design using Autodesk Inventor software and analyze the structural strength of the modified results through Finite Element Analysis (FEA) simulation. The research methods used include observation, interviews with the technical team, and the application of design analysis techniques to overcome the research problems that occur. The results of the FEA analysis show that design modifications can reduce stress concentration at critical points and increase component resistance to dynamic loads. Although the proposed design is better, periodic inspections are still needed to detect damage early and ensure continued production.